Modeling and design of the new combined double-flash and binary geothermal power plant for multigeneration purposes; thermodynamic analysis. (26th May 2022) - Yilmaz, Fatih; Ozturk, Murat; Selbas, Resat
Abstract: Renewable energy sources have great importance to deal with environmental detriments. To clean and sustainable future, various design renewable energy-assisted plants are of great importance. The current study examines the design and investigation of a double-flash binary geothermal energy-powered integrated system for useful products. For the purpose of producing hydrogen, power, heating, and drying, the proposed work basically consists of two steam turbines, a transcritical carbon dioxide Rankine cycle (tCO2 -RC ), a PEM electrolyzer, a domestic water heater (DHW), and a dryer. The chief target of this research study is to develop a more efficient plant as well as multigeneration productions. Additionally, detailed parametric modeling is carried out using energetically and exergetically approaches to examine this designed plant in the context of thermodynamic analysis. The variation of some parameters that influence the plant's performance, such as geothermal water temperature, flash pressure, and ambient temperature, are parametrically investigated. Subsequently, the thermodynamic simulation results show that the advised integrated plant produces 4431 kW electrical power. Also, the amount of the hydrogen generation capacity is 0.006809 kgs −1 . The tCO2 -RC sub-plant's energetic and exergetic performance is determined as 6.18% and 27.14%, respectively. Furthermore, the suggested integrated plant's energetic and exergetic performances are 26.20% and 37.49%. From the results, it can be finalized that the integration of various systems with the geothermal power plant is successfully possible and, in this way, there will be an increase in system performances. Highlights: A new double-flash geothermal power plant is proposed. Transcritical CO2 Rankine cycle is integrated and utilized for power generation. Thermodynamic performance examination of for whole system and sub-system is conducted. Proposed total system has 26.20% energetic efficiency.